PERCEPÇÕES DOCENTES SOBRE A CRECHE NA FRONTEIRA BRASIL-BOLÍVIA: a Educação Física nas unidades públicas de Educação Infantil em Corumbá-MS​ - Marta Maria Caldeira Padilha (2023)
The main objective of this work was to investigate the perceptions of Physical Education teachers regarding their role in the nursery stage, actions linked to the Municipal Early Childhood Education Centers (Cemeis) of the Municipal Education Network (Reme) in Corumbá, a Brazilian city in the state of Mato Grosso do Sul, located on the Brazil-Bolivia border. In the region, these educational spaces cater to children in pendular situations, characterized by students who live in Bolivian border towns and study in Corumbá, Brazil. Therefore, these different border flows, the themes of Physical Education, and Early Childhood Education were the articulated focuses of investigation in this study. To this end, the methodology employed was based on Gil (2021) and was descriptive in nature. A semi-structured interview script, captured through audio recording, was used as the data collection instrument, divided into three question blocks, namely: 1) professional profile; 2) Physical Education teacher perceptions - nursery; and 3) the child and their border characteristics in Early Childhood Education. As a final analysis, the elements found in the field research were classified to aid in the reflection and discussion to link the conceptual part with the data found. As a result, some difficulties in the pedagogical approach of the teachers were identified, such as: communication; a lack of understanding of language and communication; the nursery routine with its specific child care needs; and the absence of in-service professional development for educators involved in the nursery stage. The results also pointed to the need for better monitoring of public policies for the nursery stage and the field of Physical Education to provide support for the work of Physical Education teachers, especially when considering the specificity of Cemeis and their location in a border region. Another point suggested, upon reviewing the data, is the need to establish mechanisms to assist Physical Education teachers in dealing with pendular children, particularly when considering the context of schools on the Brazil-Bolivia border. Finally, despite the investigative limitations of the study, which demonstrates the need for more in-depth research related to the subject, the results describe a complex reality about the practice of Physical Education teachers in Early Childhood Education, particularly in the nursery stage, in Corumbá, especially when considering the Brazil-Bolivia border flows and the need for greater attention to local public policies regarding the ongoing professional development of teachers in the field. Keywords: Physical Education; Border; Teacher; Nursery; Early Childhood Education.